INNOVATIONS IN THE FIELD OF MOBILE COMMUNICATIONS (Web of Technology: Multidimensional Research Journal, 2024)
In this article, we have collected the main trends in the field of mobile communication for the present and the coming years. The latest innovations in the field of mobile communication, mobile applications, and mobile technologies and their role in society are covered in detail.